Environmental and management drivers of gastrointestinal nematodes in shelter dogs across mainland Portugal revealed by ecological niche modelling - Patrícia Lopes; Martim A. Geraldes; Jacinto Gomes; Mariana Louro; Isabel Pereira da Fonseca; Mónica V. Cunha (Preventive Veterinary Medicine, 2026)

Silver-doped carbon nanotubes from model plastic waste for enhanced mild catalytic wet peroxide oxidation of bisphenol A - Adriano S. Silva; Leiddi L. Leal; Pedro Crugeira; Maria J. Afonso; Fernanda F. Roman; A. Torres-Pinto; Paloma A. Lopes; Jose L. Diaz de Tuesta; Renata Mello Giona; Ana Isabel Pereira; Adrián M.T. Silva; Helder T. Gomes (Journal of Environmental Chemical Engineering, 2026)

Co-delivery of bioactive compounds in W/O high internal phase emulsions: Stability, in vitro digestion, and cytotoxicity - Larissa Ribas Fonseca; Marisol Gouveia Dias; Ana Isabel Bourbon; Fernanda L. Ludtke; António Vicente; Miguel A. Cerqueira; Lorenzo Pastrana; Tatiana Porto dos Santos; Rosiane Lopes Cunha; Catarina Gonçalves (Food Chemistry, 2026)

The price of opportunism: Habitat- and behaviour-specific energy costs in an opportunistic predator inhabiting anthropogenic environments - Catarina S. Lopes; Manuela G. Forero; Isabel Afán; Francisco Ramírez; Joan Navarro (Estuarine, Coastal and Shelf Science, 2026)

Exploratory short-term forecasting of respiratory hospital admissions in lisbon using air-quality and meteorological data - Behrouz Nemati; Bárbara T. Silva; Farzaneh Abedian Aval; Sina Ataee; Diogo Lopes; Vânia Martins; Ana Isabel Miranda; Hélder Relvas (Atmospheric Pollution Research, 2026)

Acute toxicity of selenium nanoparticles to Daphnia magna, Danio rerio and Xenopus laevis - Victor Galhano; Ricardo J.B. Pinto; Ana Loureiro; Luís Afonso; Maria Correia; Carolina Frazão; Miguel Oliveira; Isabel Lopes; Bruno Nunes (Chemosphere, 2026)

Ractopamine under dietary protein adjustment improves growth performance and carcass traits of immunocastrated and surgically castrated pigs slaughtered 21 days after vaccination - Diego Duran Araujo; Matheus de Almeida Ferreira; Lucas Alves Rodrigues; Idael Matheus Góes Lopes; Marcelo Dourado de Lima; Luíza de Almeida Ramos; Rafaela Jorge Sarsur de Freitas Ribeiro; Hemille Antunes Ferreira Miranda; Isabel Luísa Ribeiro de Abreu Teixeira; Francisco Carlos de Oliveira Silva; Walter Motta Ferreira; Dalton de Oliveira Fontes (Tropical Animal Health and Production, 2026)
The objective of this study was to evaluate the effects of immunocastration and ractopamine hydrochloride (RAC) supplementation on growth performance and carcass traits of male pigs slaughtered 21 days after the second immunization. Sixty-four pigs (Landrace × Large White, initial body weight 103.05 ± 0.67 kg) were individually tagged and randomly assigned to a 2 × 2 factorial arrangement in a completely randomized design, consisting of two castration methods (immunocastrated vs. surgically castrated) and two dietary RAC levels (0 or 10 ppm). No castration method × RAC interactions were observed for any variable ( P > 0.05). Immunocastrated (IM) pigs exhibited 19.5% greater average daily gain (ADG) and 13% lower feed-to-gain ratio (FG) compared with surgically castrated (SC) pigs ( P < 0.05). IM pigs also showed reduced backfat thickness across all measurement sites and greater lean meat percentage, whereas SC pigs had higher carcass yield ( P < 0.05). Ractopamine supplementation under increased amino acid supply increased ADG by 13.6%, improved hot carcass weight by 3.1%, and reduced FG by 13% ( P < 0.05). Overall, immunocastration improved growth performance and carcass leanness, while RAC supplementation increased average daily gain by 13.6%, confirming its additive effect under a shortened 21-day post-immunization interval. Immunization against GnRH combined with RAC feeding represents an effective strategy for producing heavy-weight finishing pigs with improved efficiency.

Sequential recovery of fish silage lipids and proteins for biodiesel production and marine microalgae cultivation - Regina M. González-Balderas; Isabel Martínez-Apodaca; Julio C. Sacramento-Rivero; Mariela C. Lope Navarrete; Ruby Valdez-Ojeda (Algal Research, 2026)

Valorization of orange and banana peels through Yarrowia lipolytica solid-state and semi-solid fermentation - Liliana P. Araújo; Andreia Fernandes; Isabel Belo; Marlene Lopes (Biocatalysis and Agricultural Biotechnology, 2026)

Dynamic chitosan-hyaluronic acid hydrogels for extrusion printing: Combined effects of polymer molecular weight and carbon nanofillers - Ane García-García; Maialen Goyoaga; Francisco Nuño; Ana Catarina Lopes; Estíbaliz Hernáez-Laviña; Isabel Moreno-Benítez; Jose Luis Vilas-Vilela; Senentxu Lanceros; Leyre Pérez-Álvarez (Carbohydrate Polymers, 2026)

Corrigendum to “Production of sustainable aviation fuel precursors using the oleaginous yeast Rhodotorula toruloides PYCC 5615 cultivated on eucalyptus bark hydrolysate” [Biomass Bioenergy 197 (2025) 107790] - Teresa Lopes da Silva; Francisca Dutra; Susana Marques; Miguel Gomes; Paula Costa; Filipe Paradela; Frederico Castelo Ferreira; Nuno Torres Faria; Paula Mugica; Helena M. Pinheiro; Isabel Sá-Correia; Francisco Gírio (Biomass and Bioenergy, 2026)

Corrigendum to “Differential metal and metalloid contents in fresh and cooked Charu mussels (Mytella charruana) from a southeastern Brazilian estuary and associated human health risks” [Food Control 166 (2024) 110700] - Júlia Vianna de Pinho; Isabel Q. Willmer; Carlos Adam Conte-Junior; Amanda Pontes Lopes; Tatiana D. Saint’Pierre; Everton G.N. dos Santos; Rachel Ann Hauser-Davis (Food Control, 2026)

Mating behavior and preliminary evidence of putative odor-mediated interactions in Raoiella indica (Acari: Tenuipalpidae) - Maria Isabel de Oliveira Lopes Gomes; Rhaisa Chaves dos Santos; José Wagner da Silva Melo; Debora Barbosa de Lima (Experimental and Applied Acarology, 2026)
Odour and contact chemical traces play central roles in the sexual communication of mites, mediating partner encounter and recognition of the female reproductive status. We investigated the mating behavior of Raoiella indica Hirst and the role of female-associated chemical cues in male attraction. Behavioral observations were conducted under controlled laboratory conditions, and three complementary bioassays were performed: (i) detailed recording of courtship and copulation sequences, (ii) two-choice tests to evaluate male preference for arenas associated with females at different reproductive stages, and (iii) assays testing male responses to substrate-borne traces left by females. Our objective was to describe the mating sequence of R. indica and assess how odor and contact traces contribute to male. Mating followed a stereotyped sequence composed of four stages. Males showed preference only for arenas associated with teleiochrysalis females, whereas no preference was observed for virgin or mated adult females. In contrast, males were attracted to traces left by virgin females but not to those left by recently mated females. These results indicate that male orientation in R. indica is mediated by stage-specific chemical cues and that contact traces provide reliable information about female reproductive status. Overall, our findings expand knowledge of chemical communication and mating strategies in R. indica , offering new insights into the behavioral ecology of tenuipalpid mites.

Use of Palmaria palmata and Fucus vesiculosus hydrolysates for Yarrowia lipolytica biomass and erythritol production - Bruna Dias; Marlene Lopes; Isabel Belo (Algal Research, 2026)

Carbon fluxes and partitioning in Eucalyptus and Pinus plantations across a climatic gradient in Brazil - Fernanda Leite Cunha; Otávio Camargo Campoe; Cléber Rodrigo de Souza; Isaira Leite & Lopes; Yann Nouvellon; Timothy Albaugh; David R. Carter; Rafael Rubilar; Isabel Deliberari; Rachel Cook; Joannès Guillemot; Guerric Le Maire; et al. (Agricultural and Forest Meteorology, 2026)

Are all nanoplastics equally neurotoxic? Influence of size and surface functionalization on the toxicity of polystyrene nanoplastics in human neuronal cells - Carolina Mota; Ana Margarida Araújo; Maria Enea; Eulália Pereira; Ana Reis-Mendes; Rui Fernandes; Sofia Pacheco; Marlene Lúcio; Carla Martins Lopes; Isabel M.P.L.V.O. Ferreira; Márcia Carvalho (Environmental Pollution, 2026)

Spatial clustering in air quality data accuracy: assessment of low-cost sensors in Lisbon using a novel correlation-distance index - Sina Ataee; Myriam Lopes; Maria Isabel Nunes; Sónia Gouveia; Mohammad Vahidi Borji; Helder Relvas (Air Quality, Atmosphere & Health, 2026)
Effective air quality monitoring is essential for ensuring urban environmental comfort and protecting public health, especially within smart-city frameworks. In Lisbon, the performance of low-cost NO₂ and PM 10 sensors was assessed using a novel Correlation-Distance Index (CDI) coupled with Principal Component Analysis (PCA) weighting, alongside a demographic-weighted spatial association technique, benchmarked against reference monitoring stations. The analysis began by quantifying the inverse relationship between sensor–sensor correlation and Euclidean distance. This metric was then refined through the integration of PCA-derived weights and local population density, resulting in a composite CDI-PCA score assigned to each sensor. Spatial clustering of these scores identified zones of underperforming sensors, particularly in densely populated downtown and western neighborhoods. When these clusters were compared with census-block population data, there was a statistically significant association between CDI patterns and population density (χ²=406.5, p

In vitro toxicity of indoor and outdoor PM10 from a university cafeteria - Daniela Figueiredo; Estela D. Vicente; Cátia Gonçalves; Isabel Lopes; Célia A. Alves; Helena Oliveira (Atmospheric Pollution Research, 2025)

Temperature, humidity, and substrate: keys to red palm mite survival in the environment - Bruna Rafaela Monteiro Campelo; Maria Isabel de Oliveira Lopes Gomes; Antônio de Almeida Paz Neto; José Wagner da Silva Melo; Manoel Guedes Correa Gondim Júnior; Debora Barbosa de Lima (Experimental and Applied Acarology, 2025)

Exploring Chlorella honey for the improvement of energy boost hydrogels - Joana Almeida; Ana F. Bettencourt; Susana Lopes; João Paiva; Catarina Leal; Mafalda T. Santos; Helena Cardoso; Cristina Almeida; Isabel A.C. Ribeiro (Algal Research, 2025)

Comparative biodegradation of polyethylene terephthalate by two white-rot fungi: Trametes versicolor and Pleurotus sajor caju - Laura Carvalho; Isabel Lopes; Solange Magalhães; Paulo Cardoso; Cátia Venâncio (Journal of Cleaner Production, 2025)

Exposure to Fipronil Induces Behavioural Effects on Early-Life Stages of Danio rerio - Madalina Robea; Inês Domingues; Cátia Venâncio; Gabriel Plavan; Mirmag Nicoara; Alin Ciobica; Isabel Lopes (Water, Air, & Soil Pollution, 2025)
Fipronil (FIP), an insecticide widely used in crop protection, animal health, and indoor pest control, may present a significant risk factor for the environment, wildlife, and human health due to its high lipophilicity. The current research looked at the sublethal effects of FIP on Danio rerio embryos, using a novel approach that integrates two different behavioural responses of organisms: the measurement of locomotory activity after “forced” exposure to the compound and the avoidance behaviour using a “non-forced” exposure multi-compartment system. In the first approach, freshly fertilized eggs were exposed for 120 h to FIP (0, 0.03, 0.06, 0.12, 0.24, and 0.48 mg L −1 ) evaluating, in addition to locomotor activity, the survival, developmental parameters, and acetylcholinesterase (AChE) activity as a marker of neurotoxicity. In the non-forced exposure approach, the avoidance behaviour of 6 days-old larvae of D. rerio to a linear gradient of FIP (0, 0.05, 0.07, 0.11, 0.17, and 0.24 mg L −1 FIP) was assessed for a period of 4 h. In the forced exposure, FIP decreased the swimming activity (for instance the distance travelled by larvae increased 66% at 0.48 mg L −1 compared to control) and changed swimming pattern (locomotion angles denoting erratic swimming increased from 10% in the control to 30% at 0.48 mg L −1 ). Furthermore, AChE activity in FIP-exposed fish was significantly inhibited after 120 h of exposure (AChE activity was 30% inhibited in fish exposed to the highest concentration tested when compared to control). The 4-h avoidance assay indicated that organisms could not escape from the higher FIP concentration compartments. This lack of avoidance capacity suggests rapid action of FIP, impairing the locomotory capacity of larvae to move away from toxic stress. This is partly corroborated by the significant AChE depressed activity, indicative of the disruption of cholinergic pathways by FIP and consequent disruption of locomotion function, as also seen by the depressed swimming activity. In this work, the integrated analysis of the two behavioural tests highlights the potential of behavioural parameters for an accurate assessment of pesticide risks to aquatic environments, as these parameters are easily linked with ecological functions (mating, feeding, avoidance, and response to predators) with implications at the population level and that cannot be easily evaluated through conventional endpoints used in ecotoxicology (e.g., mortality).

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

The road for red raspberry seeds valorization: A comprehensive review on the chemical composition, extraction techniques, bioactivity and applications - Paloma Lopes; Isabel M.P.L.V.O. Ferreira; Sílvia Petronilho; Cláudia P. Passos (Food Chemistry, 2025)

Intracerebral hemorrhage (hemorrhagic stroke) secondary to Bothrops spp. snakebite envenomation in a horse - Ana Lívia Vasconcelos de Sousa; Davi Emanuel Ribeiro de Sousa; Isabel Luana de Macêdo; Liz de Albuquerque Cerqueira; Yasmin Nunes Godoy da Fonseca; Andressa Barbosa Oliveira; Letícia Vilela Silva das Chagas; Geisiana Barbosa Gonçalves; Hennrique Caetano Veado; Kelly Moura Keller; Antônio Carlos Lopes Câmara; Mizael Machado; et al. (Toxicon, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Improved Estimates of Biomass Expansion Factors and Root‐To‐Shoot Ratios: An Approach for Different Forest Types Across a Climatic Gradient in Brazil - Isáira Leite e Lopes; Otávio Camargo Campoe; Geovanni Malatesta Barros; Anny Francielly Ataide Gonçalves; Gabriela Gonçalves Moreira Matzner; Marco Aurelio Figura; Clayton Alcarde Alvares; Fernanda Leite Cunha; Verônica Boarini Sampaio de Rezende; James Stahl; Josiana Jussara Nazaré Basílio; Hyngrid Jaiely Araújo Félix; et al. (Global Change Biology, 2025)
Advancements in the current state of the art of the key drivers of biomass expansion factor (BEF) and the root‐to‐shoot ratio ( R ) are crucial for producing accurate information on forest biomass and carbon stocks. Hence, we compiled a nationally representative dataset encompassing diverse tree growth stages and climatic gradients. In this study, we propose models to improve BEF and R estimates at the tree level for Eucalyptus and Pinus plantations in Brazil. In general, the BEF values were more representative (91.7%) in the database than the R values (8.3%) due to the high cost of collecting coarse roots. Regarding genera, Eucalyptus was more extensively sampled (89.9%) than Pinus (10.1%), reflecting the predominance of Eucalyptus as the most widely planted genus in Brazil. The average BEF and R values calculated in this study were 1.16 and 0.22, respectively, for Eucalyptus spp. and 1.22 and 0.31, respectively, for Pinus spp. In predicting the BEFs, the random effects in the linear mixed model that significantly captured the variations in Eucalyptus and Pinus spp. were temperature and age class, respectively. The fixed effects for Eucalyptus spp. included diameter, height, and age, while for Pinus spp., they were the Köppen climate classification, species, slenderness degree, and age. R estimates were mainly influenced by precipitation and age for both genera, with slenderness and diameter specifically affecting Eucalyptus spp., and height being a driving factor for Pinus spp. Our findings discourage the use of fixed or default values for BEF and R across locations with different climates and growing conditions to reduce uncertainties in carbon accounting and greenhouse gas inventories.

PM10 exposure in beauty salons: impact on A549 cell viability, cell cycle, oxidative stress, and mutagenicity - Daniela Figueiredo; Estela D. Vicente; Cátia Gonçalves; Isabel Lopes; Célia A. Alves; Helena Oliveira (Environmental Toxicology and Pharmacology, 2025)

Production of sustainable aviation fuel precursors using the oleaginous yeast Rhodotorula toruloides PYCC 5615 cultivated on eucalyptus bark hydrolysate - Teresa Lopes da Silva; Francisca Dutra; Susana Marques; Miguel Gomes; Paula Costa; Filipe Paradela; Frederico Castelo Ferreira; Nuno Torres Faria; Paula Mugica; Helena M. Pinheiro; Isabel Sá-Correia; Francisco Gírio (Biomass and Bioenergy, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Toxicological screening of PM2.5 from wildfires involving different biomass fuels - Estela Domingos Vicente; Daniela Figueiredo; Cátia Gonçalves; Nora Kováts; Katalin Hubai; Tsend-Ayush Sainnokhoi; Ana Vicente; Helena Oliveira; Isabel Lopes; Célia Alves (Environmental Pollution, 2025)

Hydrate-based desalination process using CO2 as hydrate forming agent – Modelling and techno-economic analysis - Isabel S. Fernandes; Mariana G. Domingos; Marcelo F. Costa; Ricardo J. Santos; José Carlos B. Lopes (Desalination, 2025)

Metallic Makos: Metal and Metalloid Levels and Human Health Risks Arising from the Consumption of Shortfin Makos (Isurus oxyrinchus) from Southeastern Brazil - Júlia Vianna de Pinho; Isabel Quental Willmer; Amanda Pontes Lopes; Regina Fonsêca; Tatiana Dillenburg Saint’Pierre; Patricia Charvet; Acácio Ribeiro Gomes Tomas; Rachel Ann Hauser-Davis (Biological Trace Element Research, 2025)

Secondary metabolites of cyanobacteria from Cape Verde Archipelago act as NO donors with potential application in dermatology and cosmetics - Janaína Morone; Guilherme Scotta Hentschke; Isabel Benta Oliveira; Vitor Vasconcelos; Rosário Martins; Graciliana Lopes (Algal Research, 2025)

Long-term impacts of salinity and temperature changes on Brachionus calyciflorus populations: understanding the role of intraspecific variability - Lishani Wijewardene; Cátia Venâncio; Rui Ribeiro; Isabel Lopes (Environmental Science and Pollution Research, 2025)
Worldwide, many coastal freshwater ecosystems suffer from seawater intrusion. In addition to this stressor, it is likely that the biota inhabiting these ecosystems will also need to deal with climate change-related temperature fluctuations. The resilience of populations to long-term exposure to these stressors will depend on their genetic diversity, a key for their adaptation to changing environments. Accordingly, this study aimed to understand the long-term effects of salinity and temperature on the population density dynamics of the rotifer Brachionus calyciflorus by considering intra-specific variability. Six clonal lineages of B. calyciflorus , exhibiting differential lethal sensitivity (LC 50,24 h ) to salinity, were exposed for at least 34 days, to a control and to artificial seawater (at a conductivity corresponding to the LC 70,24 h for the most tolerant clonal lineage = 9.89 mS/cm), under three temperatures: 17, 20 (standard) and 23 °C. Long-term exposure to artificial seawater affected population densities, leading to the extirpation of some salinity-tolerant clonal lineages earlier than that of salinity-sensitive lineages. This inversion in short- and long-term sensitivity may suggest a higher susceptibility of populations when exposed to long periods of increased salinity. The negative effects caused by artificial seawater were enhanced at 17 °C and 23 °C, with an even earlier occurrence of extirpation of some clonal lineages, namely, two clonal lineages considered tolerant to artificial seawater. The results suggest the potential synergistic effects of the two abiotic stressors when combined. Overall, a lack of association between the clonal lineages’ short- and long-term sensitivity to salinity or their sensitivity to salinity under different temperature scenarios was observed. These results suggest an increased risk to the resilience of B. calyciflorus populations exposed to climate change-related scenarios of increased salinity and temperature fluctuations owing to an enhanced reduction in their genetic variability.

Bray calls emitted by common bottlenose dolphins ( Tursiops truncatus ) in offshore waters of northeastern Brazil - Alice Lima; Lara Cunha Lopes; Jéssica Fernandes de Melo; Evelyn Fróes; Rita de Cassia De Carli; Manuela Bassoi; Renata S. Sousa‐Lima; Manuel E. dos Santos; Maria Isabel Carvalho Gonçalves (Marine Mammal Science, 2025)

Tackling water contamination by oncologic drugs: Supported ionic liquids as sustainable adsorbents for cyclophosphamide removal - Rafael Francisco; Bruna Monteiro; Maria J. Santos; Francisca A. e Silva; Catia Venancio; Marcia C. Neves; Isabel Lopes; Ana C.A. Sousa; Mara G. Freire (Journal of Environmental Management, 2024)

Differential metal and metalloid contents in fresh and cooked Charu mussels (Mytella charruana) from a southeastern Brazilian estuary and associated human health risks - Júlia Vianna de Pinho; Isabel Q. Willmer; Carlos Adam Conte-Junior; Amanda Pontes Lopes; Tatiana D. Saint’Pierre; Everton G.N. dos Santos; Rachel Ann Hauser-Davis (Food Control, 2024)

Influence of polystyrene nanoplastics on the toxicity of haloperidol to amphibians: An in vivo and in vitro approach - Filipa Morais; Valérie Pires; Mónica Almeida; Manuel A. Martins; Miguel Oliveira; Isabel Lopes (Science of The Total Environment, 2024)

Nano-hydroxyapatite Pickering emulsions as edible mayonnaise-like food sauce templates: A novel approach for food design - Maria Eduarda Relvas; Larissa C. Ghirro; Isabel M. Martins; Jose Carlos B. Lopes; Madalena M. Dias; Maria Filomena Barreiro; Andreia Ribeiro (Journal of Food Engineering, 2024)

Trajectory, fate, and magnitude of continental microplastic loads to the inner shelf: A case study of the world's largest coastal shallow lagoon - Carolina Rodriguez; Pablo Silva; Laura Moreira; Larissa Zacher; Andreia Fernandes; Remi Bouyssou; Isabel Jalón-Rojas; Osmar Moller; Felipe Garcia-Rodriguez; Grasiela Lopes Leães Pinho; Elisa Fernandes (Science of The Total Environment, 2024)

Evaluation of NETmix geometrical properties on gas-liquid mass transfer performance - Paulo H. Marrocos; Isabel S. Fernandes; José C.B. Lopes; Madalena M. Dias; Ricardo J. Santos; Vítor J.P. Vilar (Journal of Environmental Chemical Engineering, 2024)

Yarrowia lipolytica growth, lipids, and protease production in medium with higher alkanes and alkenes - Sílvia M. Miranda; Isabel Belo; Marlene Lopes (World Journal of Microbiology and Biotechnology, 2024)
Two strains of Yarrowia lipolytica (CBS 2075 and DSM 8218) were first studied in bioreactor batch cultures, under different controlled dissolved oxygen concentrations (DOC), to assess their ability to assimilate aliphatic hydrocarbons (HC) as a carbon source in a mixture containing 2 g·L −1 of each alkane (dodecane and hexadecane), and 2 g·L −1 hexadecene. Both strains grew in the HC mixture without a lag phase, and for both strains, 30 % DOC was sufficient to reach the maximum values of biomass and lipids. To enhance lipid-rich biomass and enzyme production, a pulse fed-batch strategy was tested, for the first time, with the addition of one or three pulses of concentrated HC medium. The addition of three pulses of the HC mixture (total of 24 g·L −1 HC) did not hinder cell proliferation, and high protease (> 3000 U·L −1 ) and lipids concentrations of 3.4 g·L −1 and 4.3 g·L −1 were achieved in Y. lipolytica CBS 2075 and DSM 8218 cultures, respectively. Lipids from the CBS 2075 strain are rich in C16:0 and C18:1, resembling the composition of palm oil, considered suitable for the biodiesel industry. Lipids from the DSM 8218 strain were predominantly composed of C16:0 and C16:1, the latter being a valuable monounsaturated fatty acid used in the pharmaceutical industry. Y. lipolytica cells exhibited high intrinsic surface hydrophobicity (> 69 %), which increased in the presence of HC. A reduction in surface tension was observed in both Y. lipolytica cultures, suggesting the production of extracellular biosurfactants, even at low amounts. This study marks a significant advancement in the valorization of HC for producing high-value products by exploring the hydrophobic compounds metabolism of Y. lipolytica .

The study of galactomannans with different molecular weights and their ability to form microparticles suitable for pulmonary delivery - Miguel F. Galrinho; Lisete M. Silva; Guido R. Lopes; Bernardo A.C. Ferreira; Sara A. Valente; Isabel Ferreira; Benedita A. Pinheiro; Angelina S. Palma; Dmitry V. Evtuguin; José A. Lopes da Silva; Margarida Almeida; Paula Ferreira; et al. (Carbohydrate Polymers, 2024)

Assessment of silver nanoparticles' antitumor effects: Insights into cell number, viability, and morphology of glioblastoma and prostate cancer cells - Isabel Cristina Gomes Santos; Michelle Lopes de Oliveira; Renata Carvalho Silva; Celso Sant'Anna (Toxicology in Vitro, 2024)

Polyhydroxybutyrate (PHB) nanoparticles modulate metals toxicity in Hydra viridissima - Ana Santos; Miguel Oliveira; Isabel Lopes; Mónica Almeida; Cátia Venâncio (Science of The Total Environment, 2024)

Effects of Myrcia pubipetala Miq (Myrtaceae) extract on innate inflammatory response - Pâmela Pacassa Borges; Larissa Benvenutti; Aline Lana Schneider; Marcelo Rodrigo Franke Echterhoff; Bruna Gonçalves Lopes; Diogo Alexandre Siebert; Gustavo Amadeu Micke; Luciano Vitali; Michele Debiasi Alberton; Nara Lins Meira Quintão; José Roberto Santin; Isabel Daufenback Machado (Natural Product Research, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Outdoor charcoal combustion in barbecue grills: Potential cytotoxic, oxidative stress and mutagenic effects - Daniela Figueiredo; Estela D. Vicente; Cátia Gonçalves; Isabel Lopes; Helena Oliveira; Célia A. Alves (Atmospheric Environment, 2024)

Evaluation of the Anti-biofilm Efficacy of Kyotorphin Derivatives and Biosafety Assessment: In Vitro and In Vivo Investigations Targeting Bacterial and Fungal Pathogens - Isabel Chaves Silva Carvalho; Fernanda da Silva Seiffert Simões; Vitor Martins de Andrade; Dayane Batista Tada; Montserrat Heras; Eduard Bardají; Mônica Lopes Ferreira; Miguel Augusto Rico Botas Castanho; Katia Conceição (International Journal of Peptide Research and Therapeutics, 2024)

Sub-chronic exposure to paroxetine disrupts ecologically relevant behaviours in fish - Carla S.S. Ferreira; Cátia Venâncio; Mónica Almeida; Isabel Lopes; Peter Kille; Miguel Oliveira (Science of The Total Environment, 2024)

Short- and long-term toxicity of nano-sized polyhydroxybutyrate to the freshwater cnidarian Hydra viridissima - Ana Santos; Miguel Oliveira; Mónica Almeida; Isabel Lopes; Cátia Venâncio (Science of The Total Environment, 2024)

High-resolution multi-scale air pollution system: Evaluation of modelling performance and emission control strategies - Diogo Lopes; Joana Ferreira; Sandra Rafael; Ka In Hoi; Xin Li; Yuan Liu; Ka-Veng Yuen; Kai Meng Mok; Ana Isabel Miranda (Journal of Environmental Sciences, 2024)

Enhancing the taxonomic delimitation of Lippia origanoides Kunth (Verbenaceae) by analyzing volatile terpenes and molecular markers in micropropagated accessions - Laís M. Frattini; Arthur A. Oliveira; Jhoão S. Kotsubo; Íris B. Gorne; Isabel C. Silva; Jober C. E. Freitas; Cristiano F. Resende; Ana C. Mezzonato-Pires; Elyabe M. Matos; Juliana M. L. Lopes; Lyderson F. Viccini; Richard M. Grazul; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Reproductive isolation between two sympatric bat-pollinated Bauhinia (Leguminosae) - Sinzinando Albuquerque-Lima; Ariadna Valentina Lopes; Isabel Cristina Machado (Journal of Plant Research, 2024)

Behavioural, developmental and biochemical effects in zebrafish caused by ibuprofen, irgarol and terbuthylazine - Mohammed Ariful Islam; Isabel Lopes; Inês Domingues; Daniel C.V.R. Silva; Julián Blasco; Joana Luísa Pereira; Cristiano V.M. Araújo (Chemosphere, 2023)

Organic acids in bread-making affecting gluten structure and digestibility - Ana Elisa Ramos Magalhães; Maria Isabel Landim Neves; Bruna dos Reis Gasparetto; Fernando Divino Oliveira Júnior; Larissa Ribas Fonseca; Caroline Joy Steel; Rosiane Lopes da Cunha (Food Research International, 2023)

Environmental coastal research: a systematic review for Azores and Cabo Verde, two peripherical Macaronesian archipelagos - Ander Larrea; Paulo Torres; Cristina Seijo; Maria Anunciação Ventura; Ana Cristina Costa; Manuela Isabel Parente; Evandro Lopes; Danko Castaño; Andrea Zita Botelho (Frontiers in Marine Science, 2023)
There is a strong link between humans and the coastal zone, as it provides important services and resources. This paper aims to determine the existing environmental coastal research status in the Azores and Cabo Verde since research is essential for any decision support system. Some tools are fundamental to ensure the viability of the marine environments, such as Integrated Coastal Zone Management (ICZM), Marine Protected Areas (MPAs), and Marine Spatial Planning (MSP), which rely on existing knowledge. Effective implementation of marine plans can increase by developing a multi-perspective knowledge approach. This paper presents a systematic review of the archipelagos of the Azores and Cabo Verde through a comparative meta-analysis of the literature based on the PRISMA report to better understand the focus and status of research related to coastal zones, within and outside MPAs, along with marine spatial planning and management in the two socio-economic contexts. This will help to identify common issues, trends over the years, successes, and challenges, highlighting the specific interests of each country, identifying the knowledge gaps, promoting mutual learning, and pointing out possible paths for future convergence toward sustainable use of the ecosystems and conservation goals. Differences were found between the research made in both archipelagos, lacking research on important disciplines (reproduction, behavior, population dynamics, climate change, etc.), in Cabo Verde, compared to the Azores. This study also reveals that some research fields still need to be pushed forward to have broader knowledge in both areas.

Soil pH influences the toxicity of Basamid® eluates to non-target species of primary consumers - Antonieta Gabriel; Cátia Venâncio; José Paulo Sousa; Sara Leston; Fernando Ramos; Amadeu M.V.M. Soares; Isabel Lopes (Aquatic Toxicology, 2023)

Pre-exposure to seawater or chloride salts influences the avoidance-selection behavior of zebrafish larvae in a conductivity gradient - Cátia Venâncio; Rui Ribeiro; Isabel Lopes (Environmental Pollution, 2023)

Fighting drift sands with pine trees: Reforestation of coastal areas of NW Portugal at the end of eighteenth century - Ana Isabel Lopes (Journal of Coastal Conservation, 2023)
From the late Middle Ages until the end of the nineteenth century, the northwest coast of Portugal was severely affected by drift sands, which led to the disappearance of villages or forced the population to migrate or suffer several losses. Along the northern European Atlantic coast, the most effective response to the drift sands was the reforestation of coastal areas, starting from the end of the eighteenth century and in the nineteenth century. In the northwest coast of Portugal, until the end of the nineteenth century, coastal planning and management was mainly the responsibility of local civil, manorial, and religious institutions. Based on historical sources, monastic institutions' forest management actions will be analyzed, and whether these initiatives successfully made communities in north-western Portugal less vulnerable to drift sands. This study will also allow a comparison of how the coastal landscape in the Portuguese Northwest has been reshaped and managed over two centuries, the profound impacts caused by tourism activities in the second half of the twentieth century, and the implementation of coastal management plans by the Portuguese State from 1993 onwards.

Status and perspectives of blue economy sectors across the Macaronesian archipelagos - Yaiza Fernández-Palacios; Sadasivam Kaushik; Andrej Abramic; Víctor Cordero-Penín; Alejandro García-Mendoza; Alberto Bilbao-Sieyro; Yeray Pérez-González; Pedro Sepúlveda; Isabel Lopes; Carlos Andrade; Natacha Nogueira; Gilberto P. Carreira; et al. (Journal of Coastal Conservation, 2023)
The global economy is increasingly focusing on the Oceans to meet its needs, for which maritime spatial planning is being fostered to promote this is done sustainably. Thus, assessing the current state and future development trends of the maritime sectors is key to evaluating the performance of the planning process. This is the aim of this study, in which the main maritime sectors related to the blue economy present in the archipelagos of the European Macaronesia Sea Basin, i.e. the Azores and Madeira (Portugal), and the Canary Islands (Spain), were identified and studied. The following maritime sectors were analysed: fisheries, marine aquaculture, marine biotechnology, coastal and maritime tourism, maritime transport, ship repair and maintenance, extraction of aggregates, deep-sea mining, offshore oil and gas, renewable ocean energies, and desalination. As part of the PLASMAR project, partners undertook in 2017–19 a literature review gathering scientific papers, official statistics and reports, which were complemented by interviews with experts from the economic sectors and public administration departments. Results show that while some maritime sectors are well established, others are emerging sectors with varying long-term growth potential. Besides, development patterns vary across the archipelagos. This study represents the first effort in the Macaronesia Sea Basin to set the basis of the current and future development conditions of the blue economy in applicability to maritime spatial planning processes at a regional level. The future post-pandemic context will provide a unique opportunity to promote the blue economy sectors and activities through the support provided by the EU Green Deal and Recovery and Resilience Plans, as well as with the actions envisioned under the United Nations Decade of Ocean Science for Sustainable Development (2021–2030). The European Macaronesia example –given its wide maritime territory, commitment, and capacities in terms of expertise and networking– presents a great potential to act as a good practice to extrapolate the new approach for a sustainable blue economy to other similar geographical settings such as island regions/states.

Bat pollination in the Caatinga: A review of studies and peculiarities of the system in the new world's largest and most diverse seasonally dry tropical forest - Arthur Domingos-Melo; Sinzinando Albuquerque-Lima; Ugo Mendes Diniz; Ariadna Valentina Lopes; Isabel Cristina Machado (Flora, 2023)

Combined effects of two abiotic stressors (salinity and temperature) on a laboratory-simulated population of Daphnia longispina - Cátia Venâncio; Lishani Wijewardene; Rui Ribeiro; Isabel Lopes (Hydrobiologia, 2023)
Sea level rise is expected to continue apace, with a concomitant rise in temperature on the globe's surface. Natural populations genetic pool compromised by increased salinity would contribute to decrease resilience under future temperature changes. Therefore, this work aimed to understand the long-term effects of salinization on the genetic diversity of a cladoceran-simulated laboratory population under different temperature regimes. For that, six clonal lineages of the cladoceran Daphnia longispina were chosen based on their reported differential lethal sensitivity (LC x ) to salinity. The chronic experiment was initiated when each individual clonal lineage reached the population’s carrying capacity, and then were exposed to the LC 70,48 h for the most tolerant clonal lineage of D. longispina (corresponding to 5.91 mS/cm) to 17°C, 20°C and 23°C for at least 30 days. Salinity affected D. longispina survival and reproduction, with the disappearance of salt-tolerant earlier than salt-sensitive lineages after chronic exposures. Different sensitivity ranks were observed for clonal lineages when comparing short-term and chronic survival, most probably due to acclimation-driven population recovery. Non-optimal tested temperatures (17°C and 23°C) enhanced negative effects of salinity through loss of the most sensitive clonal lineages, suggesting a potential future synergistic effect between both abiotic factors.

Effects of petroleum-based and biopolymer-based nanoplastics on aquatic organisms: A case study with mechanically degraded pristine polymers - Miguel Tamayo-Belda; Cátia Venâncio; Francisca Fernandez-Piñas; Roberto Rosal; Isabel Lopes; Miguel Oliveira (Science of The Total Environment, 2023)

Authentication of incense (Pittosporum undulatum Vent.) honey from the Azores (Mel dos Açores) by a novel real-time PCR approach - Ana R. Lopes; Mónica B.M.V. Moura; Liliana Grazina; Joana Costa; Joana S. Amaral; M. Alice Pinto; Isabel Mafra (Food Chemistry, 2023)

Ecotoxicity of non- and PEG-modified lanthanide-doped nanoparticles in aquatic organisms - Anna Ekner-Grzyb; Natalia Jurga; Cátia Venâncio; Tomasz Grzyb; Bartosz F. Grześkowiak; Isabel Lopes (Aquatic Toxicology, 2023)

DNA metabarcoding to assess prey overlap between tuna and seabirds in the Eastern tropical Atlantic: Implications for an ecosystem-based management - Ana Rita Carreiro; Jaime A. Ramos; Vanessa A. Mata; Nathalie M. Almeida; Isabel Rodrigues; Ivo dos Santos; Diana M. Matos; Pedro M. Araújo; Teresa Militão; Jacob González-Sólis; Vitor H. Paiva; Ricardo Jorge Lopes (Marine Environmental Research, 2023)

Ecotoxicity of eluates obtained from Basamid® contaminated soils is pH dependent: A study with Hydra viridissima, Xenopus laevis and Danio rerio - Antonieta Gabriel; Cátia Venâncio; José Paulo Sousa; Sara Leston; Fernando Ramos; Amadeu M.V.M. Soares; Isabel Lopes (Science of The Total Environment, 2023)

Assessing the risks of capecitabine and its active metabolite 5-fluorouracil to freshwater biota - Cátia Venâncio; Bruna Monteiro; Isabel Lopes; Ana C. A. Sousa (Environmental Science and Pollution Research, 2023)
Capecitabine (CAP, prodrug) and 5-fluorouracil (5-FU, its active metabolite) are two of the most prominent cytostatics, for which no clear picture can be drawn regarding potential concentrations of effect for freshwater biota, with CAP being grouped in the least studied cytostatic, whereas 5-FU has been classified as of no and of high environmental risk. Accordingly, the present work aimed to assess the ecotoxicity of CAP and 5-FU in three freshwater species, which included a 72-h assay with the producer Raphidocelis subcapitata ; a 96-h assay with the invertebrate secondary consumer Hydra viridissima ; and a 96-h assay with embryos of the vertebrate secondary consumer Danio rerio . The following endpoints were monitored: yield and population growth rate for the algae; mortality, morphological alterations, and post-exposure feeding rates for the cnidarian; and mortality, hatching, and malformations for the fish. Overall, organisms’ sensitivity to CAP decreased in the following order: R. subcapitata > H. viridissima > D. rerio , whereas for 5-FU, it decreased in the following order: H. viridissima > D. rerio > R. subcapitata . For CAP, no median lethal effective concentrations (LC/EC 50 ) were possible to compute for D. rerio , with no significant mortality or malformations registered in embryos exposed at concentrations up to 800 mg L −1 . For R. subcapitata , the EC 50 s were 0.077 and 0.63 mg L −1 for yield and growth rate, respectively, and for H. viridissima , the EC 50,30 min for feeding was 22.0 mg L −1 . For 5-FU, no EC 50s could be computed for R. subcapitata , whilst the EC 50s for H. viridissima mortality and feeding were 55.4 and 67.9 mg L −1 , respectively, and for D. rerio , the LC 50,96 h and EC 50,96 h (hatching and abnormalities) were 4546, 4100, and 2459 mg L −1 , respectively. Assuming similar modes of action for both compounds and their co-occurrence, the combined risk quotient of the two chemicals was determined to be 7.97, which represents a risk for freshwater biota. Anticipating the increased consumption of these compounds and cancer development trends worldwide, these impacts may be further aggravated.

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

First metal and metalloid study assessment for the Black Triggerfish Melichthys niger (Bloch, 1786): Baseline data from a pristine South Atlantic oceanic island - Rachel Ann Hauser-Davis; Isabella C. Bordon; Isabel Q. Willmer; Amanda P. Lopes; Sérgio C. Moreira; Tatiana D. Saint'Pierre; Marcelo Vianna (Marine Pollution Bulletin, 2023)

Soil pH matters in the ecotoxicity of Basamid® to freshwater microalgae and macrophytes - Antonieta Gabriel; Cátia Venâncio; José Paulo Sousa; Sara Leston; Fernando Ramos; Amadeu M.V.M. Soares; Isabel Lopes (Science of The Total Environment, 2023)

Activation of persulfate using copper oxide nanoparticles for the degradation of Rhodamine B containing effluents: Degradation efficiency and ecotoxicological studies - Mahsa Davarazar; Mohammadreza Kamali; Cátia Venâncio; Antonieta Gabriel; Tejraj M. Aminabhavi; Isabel Lopes (Chemical Engineering Journal, 2023)

Forward-looking on new microbial consortia: Combination of rot fungi and rhizobacteria on plant growth-promoting abilities - Bruno Carneiro; Paulo Cardoso; Etelvina Figueira; Isabel Lopes; Cátia Venâncio (Applied Soil Ecology, 2023)

Adding knowledge to the design of safer hydrophobically modified poly(acrylic) acids: an ecotoxicological approach - Jorge Tavares; Cátia Venâncio; Cláudia Duarte; Filipe E. Antunes; Isabel Lopes (Environmental Science and Pollution Research, 2023)

Effects of aqueous extracts of wildfire ashes on tadpoles of Pelophylax perezi: Influence of plant coverage - Diogo Santos; Nelson Abrantes; Isabel Campos; Inês Domingues; Isabel Lopes (Science of The Total Environment, 2023)

Redox homeostasis at SAM: a new role of HINT protein - Emanoelly Roberta de Carvalho Morais; Nathalia Maira Cabral de Medeiros; Francinaldo Leite da Silva; Isabel Andrade Lopes de Sousa; Izamara Gesiele Bezerra de Oliveira; Carlos Henrique Salvino Gadelha Meneses; Katia Castanho Scortecci (Planta, 2023)

Using low-cost sensors to assess real-time comfort and air quality patterns in indoor households - Johnny Reis; Diogo Lopes; Daniel Graça; Ana Patrícia Fernandes; Ana Isabel Miranda; Myriam Lopes (Environmental Science and Pollution Research, 2023)

Changes in land use of temperate forests associated to avocado production in Mexico: Impacts on soil properties, plant traits and insect-plant interactions - Abel Pérez-Solache; Marcela Sofía Vaca-Sánchez; Yurixhi Maldonado-López; Maurício Lopes De Faria; Magno Augusto Zazá Borges; Marcílio Fagundes; Ken Oyama; María Isabel Méndez-Solórzano; Joan Sebastian Aguilar-Peralta; Rafael Hernández-Guzmán; Pablo Cuevas-Reyes (Agricultural Systems, 2023)

Differential sensitivity of aquatic life stages of Pelophylax perezi to an acidic metal-contaminated effluent - Sara Peixoto; Bárbara Santos; Graça Lopes; Patrícia Dias-Pereira; Isabel Lopes (Environmental Science and Pollution Research, 2022)

Genetic modulation of anemia severity, hemolysis level, and hospitalization rate in Angolan children with Sickle Cell Anemia - Isabel Germano; Brígida Santos; Mariana Delgadinho; Catarina Ginete; Pedro Lopes; Ana Paula Arez; Miguel Brito; Paula Faustino (Molecular Biology Reports, 2022)

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

Contributions towards the hazard evaluation of two widely used cytostatic drugs - Bruna Monteiro; Cátia Venâncio; Rafael Francisco; Ana C. A. Sousa; Isabel Lopes (Environmental Science and Pollution Research, 2022)

Mutagenicity of PM10-bound PAHs from non-exhaust sources - Estela Domingos Vicente; Isabel Lopes; Daniela Figueiredo; Cátia Gonçalves; Ana Vicente; Célia Alves (Air Quality, Atmosphere & Health, 2022)

Assessing Stress Response in Lizards from Agroecosystems with Different Management Practices - Emanuele Fasola; Marta Biaggini; Manuel E. Ortiz-Santaliestra; Sara Costa; Bárbara Santos; Isabel Lopes; Claudia Corti (Bulletin of Environmental Contamination and Toxicology, 2022)

Cytotoxicity and mutagenicity of particulate matter from the open burning of pruning wastes - Estela D. Vicente; Daniela Figueiredo; Cátia Gonçalves; Ana Vicente; Isabel Lopes; Helena Oliveira; Célia A. Alves (Air Quality, Atmosphere & Health, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Effects of Long-Term Exposure to Increased Salinity on the Amphibian Skin Bacterium Erwinia toletana - Antonieta Gabriel; Sara Costa; Isabel Henriques; Isabel Lopes (Archives of Environmental Contamination and Toxicology, 2021)

Microbial valorization of waste cooking oils for valuable compounds production – a review - Marlene Lopes; Sílvia M. Miranda; Isabel Belo (Critical Reviews in Environmental Science and Technology, 2020)

Factorial optimization of upstream process for Cyanobium sp. pigments production - Fernando Pagels; Daniel Salvaterra; Helena M Amaro; Graciliana Lopes; Isabel Sousa-Pinto; Vitor Vasconcelos; A. Catarina Guedes (Journal of Applied Phycology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bioactive potential of Cyanobium sp. pigment-rich extracts - Fernando Pagels; Daniel Salvaterra; Helena M. Amaro; Graciliana Lopes; Isabel Sousa-Pinto; Vitor Vasconcelos; A. Catarina Guedes (Journal of Applied Phycology, 2020)

Modelling air quality levels of regulated metals: limitations and challenges - Joana Ferreira; Diogo Lopes; Sandra Rafael; Hélder Relvas; Susana Marta Almeida; Ana Isabel Miranda (Environmental Science and Pollution Research, 2020)

Climate-Change Adaptation Framework for Multiple Urban Areas in Northern Portugal - Sílvia Coelho; Sandra Rafael; Miguel Coutinho; Alexandra Monteiro; João Medina; Susana Figueiredo; Sofia Cunha; Myriam Lopes; Ana Isabel Miranda; Carlos Borrego (Environmental Management, 2020)

Challenges for contact recreation in a tropical urban lake: assessment by a water quality index - Frederico Azevedo Lopes; Rob Davies-Colley; Júlia Piazi; Juliana Souza Silveira; Andrea Coelho Leite; Natália Isabel Azevedo Lopes (Environment, Development and Sustainability, 2020)

Downscaling projections of climate change in Sao Tome and Principe Islands, Africa - Sin Chan Chou; André de Arruda Lyra; Jorge Luís Gomes; Daniel Andrés Rodriguez; Minella Alves Martins; Nicole Costa Resende; Priscila da Silva Tavares; Claudine Pereira Dereczynski; Isabel Lopes Pilotto; Alessandro Marques Martins; Luís Felipe Alves de Carvalho; José Luiz Lima Onofre; et al. (Climate Dynamics, 2020)

It's raining fragrant nectar in the Caatinga: evidence of nectar olfactory signaling in bat‐pollinated flowers - Arthur Domingos‐Melo; Paulo Milet‐Pinheiro; Daniela Maria do Amaral Ferraz Navarro; Ariadna Valentina Lopes; Isabel Cristina Machado (Ecology, 2020)

Host dispersal shapes the population structure of a tick‐borne bacterial pathogen - Ana Cláudia Norte; Gabriele Margos; Noémie S. Becker; Jaime Albino Ramos; Maria Sofia Núncio; Volker Fingerle; Pedro Miguel Araújo; Peter Adamík; Haralambos Alivizatos; Emilio Barba; Rafael Barrientos; Laure Cauchard; et al. (Molecular Ecology, 2020)
Birds are hosts for several zoonotic pathogens. Because of their high mobility, especially of longdistance migrants, birds can disperse these pathogens, affecting their distribution and phylogeography. We focused on Borrelia burgdorferi sensu lato, which includes the causative agents of Lyme borreliosis, as an example for tick‐borne pathogens, to address the role of birds as propagation hosts of zoonotic agents at a large geographical scale. We collected ticks from passerine birds in 11 European countries. B . burgdorferi s.l. prevalence in Ixodes spp. was 37% and increased with latitude. The fieldfare Turdus pilaris and the blackbird T. merula carried ticks with the highest Borrelia prevalence (92 and 58%, respectively), whereas robin Erithacus rubecula ticks were the least infected (3.8%). Borrelia garinii was the most prevalent genospecies (61%), followed by B. valaisiana (24%), B. afzelii (9%), B. turdi (5%) and B. lusitaniae (0.5%). A novel Borrelia genospecies “ Candidatus Borrelia aligera” was also detected. Multilocus sequence typing ( MLST ) analysis of B. garinii isolates together with the global collection of B. garinii genotypes obtained from the Borrelia MLST public database revealed that: (a) there was little overlap among genotypes from different continents, (b) there was no geographical structuring within Europe, and (c) there was no evident association pattern detectable among B. garinii genotypes from ticks feeding on birds, questing ticks or human isolates. These findings strengthen the hypothesis that the population structure and evolutionary biology of tick‐borne pathogens are shaped by their host associations and the movement patterns of these hosts.

Impacts of bamboo spreading: a review - Sarah Tanganeli Buziquia; Paulo Victor Freitas Lopes; Aleska Kaufmann Almeida; Isabel Kaufmann de Almeida (Biodiversity and Conservation, 2019)

Validity of fish, birds and mammals as surrogates for amphibians and reptiles in pesticide toxicity assessment - Manuel E. Ortiz-Santaliestra; Joao P. Maia; Andrés Egea-Serrano; Isabel Lopes (Ecotoxicology, 2018)

Spatial distance and climate determine modularity in a cross‐biomes plant–hummingbird interaction network in Brazil - Andréa Cardoso Araujo; Ana M. Martín González; Brody Sandel; Pietro K. Maruyama; Erich Fischer; Jeferson Vizentin‐Bugoni; Francielle Paulina de Araújo; Aline Góes Coelho; Rogério Rodrigues Faria; Glauco Kohler; Flor Maria Guedes Las‐Casas; Ariadna Valentina Lopes; et al. (Journal of Biogeography, 2018)
Aim We examined the effects of space, climate, phylogeny and species traits on module composition in a cross‐biomes plant–hummingbird network. Location Brazil, except Amazonian region. Methods We compiled 31 local binary plant–hummingbird networks, combining them into one cross‐biomes metanetwork. We conducted a modularity analysis and tested the relationship between species’ module membership with traits, geographical location, climatic conditions and range sizes, employing random forest models. We fitted reduced models containing groups of related variables (climatic, spatial, phylogenetic, traits) and combinations of groups to partition the variance explained by these sets into unique and shared components. Results The Brazilian cross‐biomes network was composed of 479 plant and 42 hummingbird species, and showed significant modularity. The resulting six modules conformed well to vegetation domains. Only plant traits, not hummingbird traits, differed between modules, notably plants’ growth form, corolla length, flower shape and colour. Some modules included plant species with very restricted distributions, whereas others encompassed more widespread ones. Widespread hummingbirds were the most connected, both within and between modules, whereas widespread plants were the most connected between modules. Among traits, only nectar concentration had a weak effect on among‐module connectivity. Main conclusions Climate and spatial filters were the main determinants of module composition for hummingbirds and plants, potentially related to resource seasonality, especially for hummingbirds. Historical dispersal‐linked contingency, or environmental variations not accounted for by the explanatory factors here evaluated, could also contribute to the spatial component. Phylogeny and morphological traits had no unique effects on the assignment of species to modules. Widespread species showed higher within‐ and/or among‐module connectivity, indicating their key role connecting biomes, and, in the case of hummingbirds, communities within biomes. Our results indicate that biogeography and climate not only determine the variation of modularity in local plant–animal networks, as previously shown, but also affect the cross‐biomes network structure.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Life paths of patients with transthyretin-related familial amyloid polyneuropathy Val30Met: a descriptive study - Alice Lopes; Alexandra Sousa; Isabel Fonseca; Margarida Branco; Carla Rodrigues; Teresa Coelho; Jorge Sequeiros; Paula Freitas (Journal of Community Genetics, 2018)

Gene expression and activity of antioxidant enzymes in rice plants, cv. BRS AG, under saline stress - Tatiana Rossatto; Marcelo Nogueira do Amaral; Letícia Carvalho Benitez; Isabel Lopes Vighi; Eugenia Jacira Bolacel Braga; Ariano Martins de Magalhães Júnior; Mara Andrade Colares Maia; Luciano da Silva Pinto (Physiology and Molecular Biology of Plants, 2017)

Evidence of phytotoxicity in a fast-growing shrub useful for savanna restoration in Central Brazil - Polliana Gomes Lopes; Karina Alacid Salles; Sarah C. Caldas Oliveira; Alexandre Bonesso Sampaio; Isabel Belloni Schmidt (Brazilian Journal of Botany, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Bee pollination and evidence of substitutive nectary in Anadenanthera colubrina (Leguminosae-Mimosoideae) - Laís Angélica Borges; Isabel Cristina Machado; Ariadna Valentina Lopes (Arthropod-Plant Interactions, 2017)

Evaluation of stability and validation of reference genes for RT-qPCR expression studies in rice plants under water deficit - Priscila Ariane Auler; Letícia Carvalho Benitez; Marcelo Nogueira do Amaral; Isabel Lopes Vighi; Gabriela dos Santos Rodrigues; Luciano Carlos da Maia; Eugenia Jacira Bolacel Braga (Journal of Applied Genetics, 2017)

Mutagenicity assessment of aerosols in emissions from domestic combustion processes - Nuno Canha; Isabel Lopes; Estela Domingos Vicente; Ana M. Vicente; Benjamin A. Musa Bandowe; Susana Marta Almeida; Célia A. Alves (Environmental Science and Pollution Research, 2017)

Bridging of cryptic Borrelia cycles in European songbirds - Dieter Heylen; Aleksandra Krawczyk; Isabel Lopes de Carvalho; Maria Sofia Núncio; Hein Sprong; Ana Cláudia Norte (Environmental Microbiology, 2017)
Summary The principal European vector for Borrelia burgdorferi s.l., the causative agents of Lyme disease, is the host‐generalist tick Ixodes ricinus . Almost all terrestrial host‐specialist ticks have been supposed not to contribute to the terrestrial Borrelia transmission cycles. Through an experiment with blackbirds, we show successful transmission by the widespread I. frontalis , an abundant bird‐specialized tick that infests a broad range of songbirds. In the first phase of the experiment, we obtained Borrelia ‐infected I. frontalis (infection rate: 19%) and I. ricinus (17%) nymphs by exposing larvae to wild blackbirds that carried several genospecies ( Borrelia turdi , B. valaisiana , B. burgdorferi s.s.). In the second phase, pathogen‐free blackbirds were exposed to these infected nymphs. Both tick species were able to infect the birds, as indicated by the analysis of xenodiagnostic I. ricinus larvae which provided evidence for both co‐feeding and systemic transmission (infection rates: 10%‐60%). Ixodes frontalis was shown to transmit B. turdi spirochetes, while I. ricinus transmitted both B. turdi and B. valaisiana . Neither species transmitted B. burgdorferi s.s. European enzootic cycles of Borrelia between songbirds and their ornithophilic ticks do exist, with I. ricinus potentially acting as a bridging vector towards mammals, including man.

Using dendritic cells to evaluate how Burkholderia cenocepacia clonal isolates from a chronically infected cystic fibrosis patient subvert immune functions - M. Guadalupe Cabral; Marília Pereira; Zélia Silva; Inês Iria; Carla Coutinho; Andreia Lopes; Isabel Sá-Correia; Paula A. Videira (Medical Microbiology and Immunology, 2017)

Performance of Lynch syndrome predictive models in quantifying the likelihood of germline mutations in patients with abnormal MLH1 immunoexpression - Verónica Cabreira; Carla Pinto; Manuela Pinheiro; Paula Lopes; Ana Peixoto; Catarina Santos; Isabel Veiga; Patrícia Rocha; Pedro Pinto; Rui Henrique; Manuel R. Teixeira (Familial Cancer, 2017)

Correlation of proline content and gene expression involved in the metabolism of this amino acid under abiotic stress - Letícia Carvalho Benitez; Isabel Lopes Vighi; Priscila Ariane Auler; Marcelo Nogueira do Amaral; Gabriela Peres Moraes; Gabriela dos Santos Rodrigues; Luciano Carlos da Maia; Ariano Martins de Magalhães Júnior; Eugenia Jacira Bolacel Braga (Acta Physiologiae Plantarum, 2016)

Hydrolytic-Acidogenic Fermentation of Organic Solid Waste for Volatile Fatty Acids Production at Different Solids Concentrations and Alkalinity Addition - Tânia Gameiro; Maria Lopes; Rita Marinho; Pompilio Vergine; Helena Nadais; Isabel Capela (Water, Air, & Soil Pollution, 2016)

Mutagenicity assessment of aerosols in emissions from domestic combustion processes - Nuno Canha; Isabel Lopes; Estela Domingos Vicente; Ana M. Vicente; Benjamin A. Musa Bandowe; Susana Marta Almeida; Célia A. Alves (Environmental Science and Pollution Research, 2016)

A Convenient Trip: an Analysis of the Impact of Hitchhiker Ants on Forager Transport Rates - Isabel Neto Hastenreiter; Tatiane Archanjo de Sales; Laila Fieto Ribeiro; Juliane Floriano Santos Lopes (Journal of Insect Behavior, 2016)

Characterisation of Isospora lusitanensis n. sp. (Apicomplexa: Eimeriidae) from the Eurasian blackbird Turdus merula Linnaeus (Passeriformes: Turdidae) in mainland Portugal - Sergian Vianna Cardozo; Bruno Pereira Berto; Isabel Pereira da Fonseca; André Tomás; Fátima Regina P. B. Thode; Carlos Wilson G. Lopes (Systematic Parasitology, 2015)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Olive Oil Mill Wastewater to Volatile Fatty Acids: Statistical Study of the Acidogenic Process - Tânia Gameiro; Fátima Sousa; Flávio C. Silva; Cátia Couras; Maria Lopes; Vitória Louros; Helena Nadais; Isabel Capela (Water, Air, & Soil Pollution, 2015)

Suitability of enzymatic markers to assess the environmental condition of natural populations of Gambusia affinis and Daphnia magna—a case study - Inês Domingues; Cátia S. A. Santos; Nuno G. C. Ferreira; Luísa Machado; Rhaul Oliveira; Abel Ferreira; Isabel Lopes; Susana Loureiro; Amadeu M. V. M. Soares (Environmental Monitoring and Assessment, 2015)

V S profile: measured versus empirical correlations—a Lower Tagus river valley example - Isabel Lopes; Jaime A. Santos; Rui Carrilho Gomes (Bulletin of Engineering Geology and the Environment, 2014)

A Multidisciplinary Approach to Evaluate the Efficiency of a Clean-Up Technology to Remove Mercury from Water - Cláudia B. Lopes; Isabel Lopes; Luciana S. Rocha; Armando C. Duarte; Amadeu M. V. M. Soares; João Rocha; Eduarda Pereira (Bulletin of Environmental Contamination and Toxicology, 2014)

Dioecy in the Caatinga, a Brazilian tropical dry forest: typical reproductive traits of a low frequent sexual system - Sheila Milena Soares; Isabel Cristina Machado; Antonio Venceslau Aguiar; Ariadna Valentina Lopes (Plant Systematics and Evolution, 2014)

Reproductive ecology of Ameroglossum pernambucense (Scrophulariaceae): is this ornithophilous and threatened shrub highly adapted to a naturally fragmented habitat? - Artur Maia Wanderley; Ariadna Valentina Lopes; Isabel Cristina Machado (Plant Systematics and Evolution, 2014)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Contaminant driven genetic erosion and associated hypotheses on alleles loss, reduced population growth rate and increased susceptibility to future stressors: an essay - Rui Ribeiro; Isabel Lopes (Ecotoxicology, 2013)

Nanoscale materials and their use in water contaminants removal—a review - Iram Mohmood; Cláudia Batista Lopes; Isabel Lopes; Iqbal Ahmad; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2013)

Borrelia garinii and Francisella tularensis subsp. holarctica detected in migratory shorebirds in Portugal - Isabel Lopes de Carvalho; Líbia Zé-Zé; Ana Sofia Alves; Sara Pardal; Ricardo Jorge Lopes; Luísa Mendes; Maria Sofia Núncio (European Journal of Wildlife Research, 2012)

Reproductive isolation between diploid and tetraploid cytotypes of Libidibia ferrea (= Caesalpinia ferrea) (Leguminosae): ecological and taxonomic implications - Laís Angélica Borges; Luiz Gustavo Rodrigues Souza; Marcelo Guerra; Isabel Cristina Machado; Gwilym P. Lewis; Ariadna Valentina Lopes (Plant Systematics and Evolution, 2012)

Synchronous phenology of hawkmoths (Sphingidae) and Inga species (Fabaceae–Mimosoideae): implications for the restoration of the Atlantic forest of northeastern Brazil - Oswaldo Cruz-Neto; Isabel Cristina Machado; José Araújo Duarte; Ariadna Valentina Lopes (Biodiversity and Conservation, 2011)

Erratum to: Cleanup of atrazine-contaminated soils: ecotoxicological study on the efficacy of a bioremediation tool with Pseudomonas sp. ADP - Sónia Chelinho; Matilde Moreira-Santos; Débora Lima; Cátia Silva; Paula Viana; Sandra André; Isabel Lopes; Rui Ribeiro; Arsénio M. Fialho; Cristina A. Viegas; José P. Sousa (Journal of Soils and Sediments, 2010)

Kalirin: a novel genetic risk factor for ischemic stroke - Tiago Krug; Helena Manso; Liliana Gouveia; João Sobral; Joana M. Xavier; Isabel Albergaria; Gisela Gaspar; Manuel Correia; Miguel Viana-Baptista; Rita Moiron Simões; Amélia Nogueira Pinto; Ricardo Taipa; et al. (Human Genetics, 2010)

Cleanup of atrazine-contaminated soils: ecotoxicological study on the efficacy of a bioremediation tool with Pseudomonas sp. ADP - Sónia Chelinho; Matilde Moreira-Santos; Débora Lima; Cátia Silva; Paula Viana; Sandra André; Isabel Lopes; Rui Ribeiro; Arsénio M. Fialho; Cristina A. Viegas; José P. Sousa (Journal of Soils and Sediments, 2010)

TP53 germline mutations in Portugal and genetic modifiers of age at cancer onset - Carla Pinto; Isabel Veiga; Manuela Pinheiro; Ana Peixoto; Armando Pinto; José M. Lopes; Rui M. Reis; Carla Oliveira; Manuela Baptista; Lúcia Roque; Fernando Regateiro; Luís Cirnes; et al. (Familial Cancer, 2009)

Seasonal variations of pH, pCO2, pO2, HCO3 − and Ca2+ in the haemolymph: implications on the calcification physiology in Anodonta cygnea - Manuel Lopes-Lima; Anabela Lopes; Paula Casaca; Isabel Nogueira; António Checa; Jorge Machado (Journal of Comparative Physiology B, 2009)

Relevant principal component analysis applied to the characterisation of Portuguese heather honey - Rui C. Martins; Victor V. Lopes; Patrícia Valentão; João C.M.F. Carvalho; Paulo Isabel; Maria T. Amaral; Maria T. Batista; Paula B. Andrade; Branca M. Silva (Natural Product Research, 2008)

Smoking and gastric cancer: systematic review and meta-analysis of cohort studies - Ricardo Ladeiras-Lopes; Alexandre Kirchhofer Pereira; Amanda Nogueira; Tiago Pinheiro-Torres; Isabel Pinto; Ricardo Santos-Pereira; Nuno Lunet (Cancer Causes & Control, 2008)

Microsatellite variation and evolution of human lactase persistence - Margarida Coelho; Donata Luiselli; Giorgio Bertorelle; Ana Isabel Lopes; Susana Seixas; Giovanni Destro-Bisol; Jorge Rocha (Human Genetics, 2005)

Kinetics of inter- and intramolecular electron transfer of Pseudomonas nautica cytochrome cd 1 nitrite reductase: regulation of the NO-bound end product - Helder Lopes; Stéphane Besson; Isabel Moura; José J.G. Moura (JBIC Journal of Biological Inorganic Chemistry, 2001)

Electrochemical study on cytochrome c peroxidase from Paracoccus denitrificans: a shifting pattern of structural and thermodynamic properties as the enzyme is activated - Helder Lopes; Graham W. Pettigrew; Isabel Moura; José J. G. Moura (JBIC Journal of Biological Inorganic Chemistry, 1998)

Floral biology and reproductive ecology ofClusia nemorosa (Clusiaceae) in northeastern Brazil - Ariadna Valentina Lopes; Isabel Cristina Machado (Plant Systematics and Evolution, 1998)